Phenolic Compounds - Biological Activity 2017
DOI: 10.5772/65968
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of Skeletal Muscle Glucose Transport by Phenolic Acids

Abstract: Type 2 diabetes mellitus (T2DM) is one of the most severe public health problems in the world. In recent years, evidences show a commonness of utilization of alternative medicines such as phytomedicine for the treatment of T2DM. Phenolic acids are the most common compounds in non-flavonoid group of phenolic compounds and have been suggested to have a potential to lower the risk of T2DM. Skeletal muscle is the major organ that contributes to the pathophysiology of T2DM. Studies have shown that several phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 105 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…These include insulin‐induced stimulation of glucose uptake in peripheral tissues like muscle tissues (Aronnof et al, ). Several phenolic acids, including ferulic acid, have been shown to exhibit potent anti‐diabetic effects including modulation of glucose transport and metabolism in skeletal muscles (Egawa et al, ; Prabhakar & Doble, ). Since amadumbe and okra dry mucilage extracts showed the presence of phenolic compounds (expressed as ferulic acid equivalent), we investigated their effect on glucose uptake in isolated rat psoas muscle.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These include insulin‐induced stimulation of glucose uptake in peripheral tissues like muscle tissues (Aronnof et al, ). Several phenolic acids, including ferulic acid, have been shown to exhibit potent anti‐diabetic effects including modulation of glucose transport and metabolism in skeletal muscles (Egawa et al, ; Prabhakar & Doble, ). Since amadumbe and okra dry mucilage extracts showed the presence of phenolic compounds (expressed as ferulic acid equivalent), we investigated their effect on glucose uptake in isolated rat psoas muscle.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that amadumbe and okra dry mucilage extracts may be useful in glycemic control via modulating glucose uptake and systemic glucose disappearance. The computed GU 50 values (Concentration in mg/mL of dry mucilage extracts required to cause 50% increase of muscle glucose uptake) indicated that amadumbe mucilage (GU 50 = 0.78 ± 0.13 mg/mL) exhibited a more potent ( p = 0.0836) muscle glucose uptake effect compared to okra mucilage (GU 50 = 1.49 ± 0.18 mg/mL), perhaps due to higher ( p < 0.05) phenol content (39.91 ± 2.99 vs. 26.48 ± 1.05 mg/g) (Egawa et al, ; Prabhakar & Doble, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations